Cross-Clade Inhibition of Recombinant Human Immunodeficiency Virus Type 1 (HIV-1), HIV-2, and Simian Immunodeficiency Virus SIVcpz Reverse Transcriptases by RNA Pseudoknot Aptamers - Held, Daniel M. (American Society for Microbiology, 2007)
Reverse transcriptase (RT) remains a primary target in therapies directed at human immunodeficiency virus type 1 (HIV-1). RNA aptamers that bind RT from HIV-1 subtype B have been shown to protect human cells from infection and to reduce viral infectivity, but little is known about the sensitivity of the inhibition to amino sequence variations of the RT target. Therefore, we assembled a panel of 10 recombinant RTs from phylogenetically diverse lentiviral isolates (including strains of HIV-1, simian immunodeficiency virus SIVcpz, and HIV-2). After validating the panel by measuring enzymatic activities and inhibition by small-molecule drugs, dose-response curves for each enzyme were established for four pseudoknot RNA aptamers representing two structural subfamilies. All four aptamers potently inhibited RTs from multiple HIV-1 subtypes. For aptamers carrying family 1 pseudoknots, natural resistance was essentially all-or-none and correlated with the identity of the amino acid at position 277. In contrast, natural resistance to aptamers carrying the family 2 pseudoknots was much more heterogeneous, both in degree (gradation of 50% inhibitory concentrations) and in distribution across clades. Site-directed and subunit-specific mutagenesis identified a common R/K polymorphism within the p66 subunit as a primary determinant of resistance to family 1, but not family 2, pseudoknot aptamers. RNA structural diversity therefore translates into a nonoverlapping spectrum of mutations that confer resistance, likely due to differences in atomic-level contacts with RT.